Design and Investigation of a Nonlinear Damper Based on Energy Dissipation through Shock and Dry Friction to Suppress Critical Self-Excited Vibrations in Drilling Systems - Vincent Kulke; Georg-Peter Ostermeyer; Andreas Hohl (Shock and Vibration)
In this paper, a passive damper based on energy dissipation through shock and dry friction (shock-friction damper) is investigated regarding its design and effectiveness for damping self-excited torsional vibrations similar to those occurring in deep drilling. The results are compared to the results of conventional friction dampers. The effectiveness of the damper for different operational drilling parameters that change during the drilling process, such as the weight on the bit and the rotary speed of the bit, is analyzed. Two linear reduced order models of a drill string that are based on a complex finite element model are set up. One is reduced using the component mode synthesis and one is reduced to the identified critical mode. A lumped mass represents the inertia of a forcedly connected nonlinear damper. A combined reduced order model of the complex system and the inertia damper is introduced to investigate its dynamic motion and stability. Particular focus is on the energy flow within the dynamic system and on the change of the dissipation energy in the contact. A semi-analytical solution is derived using the harmonic balance method that is used to investigate the damping effect for various designs and operational parameters. Herein, the modal properties as well as parameters of the damper are examined regarding the damping effect and the stability of the system. Finally, the capability of the mechanism to suppress the self-excitation due to the bit–rock interaction in a drilling system is discussed, and recommendations are made with respect to the design parameters and placement of the damper.